2019
DOI: 10.3847/2041-8213/ab4a80
|View full text |Cite
|
Sign up to set email alerts
|

CHIME/FRB Discovery of Eight New Repeating Fast Radio Burst Sources

Abstract: We report on the discovery of eight repeating fast radio burst (FRB) sources found using the Canadian Hydrogen Intensity Mapping Experiment (CHIME) telescope. These sources span a dispersion measure (DM) range of 103.5-1281 pc cm −3 . They display varying degrees of activity: six sources were detected twice, another three times, and one 10 times. These eight repeating FRBs likely represent the bright and/or high-rate end of a distribution of infrequently repeating sources. For all sources, we determine sky coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(97 citation statements)
references
References 97 publications
6
90
0
1
Order By: Relevance
“…We note that the difference in w int,rest is marginal, when individual repeats of repeating FRBs are compared with that of non-repeating FRBs. A difference in observed duration between repeating and non-repeating FRBs was reported by CHIME/FRB Collaboration et al (2019c). We confirmed it with a more physically motivated parameter, w int,rest .…”
Section: Astrophysical Implications On Frb Populationssupporting
confidence: 84%
See 2 more Smart Citations
“…We note that the difference in w int,rest is marginal, when individual repeats of repeating FRBs are compared with that of non-repeating FRBs. A difference in observed duration between repeating and non-repeating FRBs was reported by CHIME/FRB Collaboration et al (2019c). We confirmed it with a more physically motivated parameter, w int,rest .…”
Section: Astrophysical Implications On Frb Populationssupporting
confidence: 84%
“…In Fig. 5 there are, at least, two repeating FRBs which change the L ν dramatically from luminous nonrepeating regime to faint repeating one, i.e., FRB 171019 and 181017.J1705+68 (Kumar et al 2019;CHIME/FRB Collaboration et al 2019c). Kumar et al (2019) reported repetitions of FRB 171019 which are 590 times fainter than the one discovered by ASKAP (brightest burst in Fig.…”
Section: Astrophysical Implications On Frb Populationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Спалах FRB 121102 був відкритий у 2014 році [7], а на даний момент є широковідомим та досліджуваним як повторюваний, загальна кількість отриманих спалахів з даного місця спостереження становить 110 шт. FRB 121102 є першим швидким радіоспалахом, що повторюється, і для котрого відомо положення з субарксекундною точністю [8][9][10] [9].…”
Section: фізико-математичні наукиunclassified
“…Most FRBs seemed to be one-off events, while some are repeating (Spitler et al 2016). CHIME has been particularly effective at finding repeating FRBs, with 17 published so far (Amiri et al 2019b;Andersen et al 2019). The origin of these FRBs remains a hot topic of debate and speculation (Platts et al 2019).…”
Section: Introductionmentioning
confidence: 99%